2008
DOI: 10.1016/j.bandc.2007.11.005
|View full text |Cite
|
Sign up to set email alerts
|

How dynamic is interhemispheric interaction? Effects of task switching on the across-hemisphere advantage

Abstract: Interaction between the cerebral hemispheres may allow both hemispheres to contribute their processing resources in order to cope efficiently with complex tasks [Banich, M. (1998). The missing link: the role of interhemispheric interaction in attentional processing. Brain and Cognition, 36,. The current study investigated whether the benefits of interhemispheric interaction arise because of top-down knowledge about the task built up over the course of a block of trials or because of the processing demands pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 16 publications
1
15
0
Order By: Relevance
“…Critically, we found an increase of the MEP amplitude 450 ms after an erroneous response. In imaging studies, activations ipsilateral to the motor response have been observed during the performance of complex motor tasks (Banich, 1998;Verstynen et al, 2005;Welcome and Chiarello, 2008). Previous studies have shown that the commission of an error engaged several regions involved in performance monitoring which resulted in either decreased activation or increased inhibition of the contralateral motor cortex (Marco-Pallare´s et al, 2008;Danielmeier and Ullsperger, 2011), which presumably might lead to the increase of excitability of the ipsilateral motor cortex shown in our data.…”
Section: Discussionsupporting
confidence: 65%
“…Critically, we found an increase of the MEP amplitude 450 ms after an erroneous response. In imaging studies, activations ipsilateral to the motor response have been observed during the performance of complex motor tasks (Banich, 1998;Verstynen et al, 2005;Welcome and Chiarello, 2008). Previous studies have shown that the commission of an error engaged several regions involved in performance monitoring which resulted in either decreased activation or increased inhibition of the contralateral motor cortex (Marco-Pallare´s et al, 2008;Danielmeier and Ullsperger, 2011), which presumably might lead to the increase of excitability of the ipsilateral motor cortex shown in our data.…”
Section: Discussionsupporting
confidence: 65%
“…Several studies have suggested that the speed of transcallosal conduction is limited in larger brains, which implies that the transfer and integration of information between both hemispheres through the corpus callosum require more time and energy in humans [3, 17]. Therefore, it may be more efficient to use one hemisphere and inhibit the other hemisphere during simple tasks (e.g., physical identity and face-matching tasks); this promotes intrahemispheric processing and brain lateralization [2, 18, 19]. …”
Section: Introductionmentioning
confidence: 99%
“…It is well established that activity in one cerebral hemisphere affects activity in the other via a rich network of interhemispheric connections (Ferbert, Priori, & Rothwell, 1992;Ilmoniemi et al, 1997), and that these interactions represent a dynamic process that can be flexibly modulated based on task demands or by exogenous stimulation (e.g., Banich, 1998;Silvanto et al, 2009;Welcome & Chiarello, 2008). Even though the functional properties of interhemispheric connections are yet to be fully elucidated, converging evidence suggests that, in many instances, these connections appear to operate in a mutually inhibitory manner.…”
Section: Interhemispheric Interactions In Strokementioning
confidence: 99%